Worldview, social sciences and modernity: a tour through their transfigurations and epistemic bifurcations - Vargas-González, Livia (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The conformation of the social sciences has been crossed not only by the discussion about its scientific status and methodological criteria of demarcation, but the conception of science and the world behind it. To the discipline dispute of sociological field will precede the dispute about what constitutes a science and what is the accompanying worldview. This article traces a journey through the process of creating, building and transfiguration of the social sciences in the modernity and contemporaneity, based on the underlying controversy in its epistemic precepts.